Using an integrated hydro-economic model to determine the drought and energy relationship in the Upper Euphrates Basin - Aytac, Ayca; Tuna, M. Cihat; Dogan, Mustafa Sahin (Iwa Publishing, 2024)
Decreasing precipitation in the Upper Euphrates Basin and the negative impact of climate change directly affect water resources and hydroelectricity generation in the basin. This basin, which contains the largest dams in terms of hydroelectricity generation potential, requires research studies to assess and characterize drought for risk prevention and mitigation applicable to water resources management. To better assess drought in the upper Euphrates Basin due to recent warming, FEHEM is developed, a hydro-economic optimization model of the integrated reservoir system of the Upper Euphrates Basin. Using a historical hydrological dataset, water management and hydroelectric operations are evaluated with a linear programming model at monthly time steps. This paper uses two different drought indices: (1) the standardized precipitation index, which is based on precipitation alone; and (2) the reconnaissance drought index, which takes into account both evaporation and precipitation. These indices were used to evaluate the impact of temporal drought characteristics in the Upper Euphrates Basin on the hydropower generation of 10 dams with a total installed capacity of over 50 MW in the basin, based on 45 years of precipitation data from more than a hundred measuring stations in the basin.
Keywords: climate change; drought index; global warming; the Upper Euphrates Basin